Особливості формування поруватого оксиду алюмінію - Ляшок, Л. В.; Шевченко, Г. С.; Лещенко, С. А.; Бровін, Олександр Юрійович (Київський національний університет технологій та дизайну, 2019)
As in our country and abroad, intensive research and development of effective methods for the synthesis of porous anodic oxides of metals is being conducted intensively. However, until now, no common approaches have been developed to explain the mechanisms of formation of ordered arrays of pores during anodic oxidation, which significantly hinders the introduction of anodic oxidation in industrial technologies for the creation of ordered nanostructures. A promising matrix for the synthesis of nanocomposites is films of porous anodic alumina, which have an ordered structure, are thermally stable, and are chemically inert with respect to most materials. By changing the composition of the electrolyte and the electrolysis mode, it is possible to control the parameters of the porous structure (diameter, length, and distance between adjacent pores). The purpose of the work is to study the features of the porous anodic aluminum oxide and its influence on pore geometry. Corrugated films are obtained in solutions of strong acids, active in relation to aluminum oxide. By changing the composition of the electrolyte, temperature and electrolysis mode it is possible to control the parameters of the porous structure (diameter, length, and distance between adjacent pores). The method of voltammetry investigated the behavior of aluminum in solutions of sulfate and oxalic acid. The influence of nature, concentration of electrolytes on the porosity of anodic oxide has been established.
Features of formation of porous aluminum oxide
Keywords: оксид алюмінію; фізико-хімічні властивості; анодний оксид алюмінію; анодна оксидна плівка; porous aluminum oxide; formation models; nanomaterial’s; orderliness; pore; oxide film; formation modes; electrolyte